A novel protocol for bacterial ghosts' preparation using tween 80 - Sameh Rabea; Mounir M. Salem-Bekhit; Fars K. Alanazi; Aymen S. Yassin; Nayera A. Moneib; Abd Elgawad M. Hashem (Elsevier, 2018)
Bacterial ghosts (BGs) can be prepared by both genetic and chemical means. Genetic method include using lysis gene E. Chemical method include incubation with numerous agents for a short time at their minimum inhibitory or minimum growth concentrations (MIC or MGC). The aim of this study is to prepare the BGs with a new protocol via exposing the bacterial cells to tween 80 for an extended period of time followed by sudden reduction of the surrounding pH. Salmonella enterica serovar typhimurium ATCC 13311 was used for this purpose. The cells were incubated in 7% v/v tween 80 solution in Muller-Hinton broth for 24 h at 37 °C then pH was decreased to 3.6 by adding lactic acid for one hour. The bacterial pellets were separated by high speed centrifugation, and then washed three times by half normal saline solution. High quality BGs were visualized by scanning electron microscopy (SEM) revealing punctured cells with intact outer shells and at least one intramembranous tunnel. The absence of vital cells was confirmed by subculturing. The release of respective amounts of proteins and DNA is another evidence of ghost's production. In addition, the integrity of cells was proved by visualization of Gram-stained cells using light microscopy. In conclusion, this new protocol is simple, economic and feasible for BGs preparation.